IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA BAGI TENAGA PENDIDIK DI MADRASAH ALIYAH AL-HILAAL TEHORU (Studi Kasus Pada Rekrutmen, Seleksi, Penempatan) - Muhammad Ali Holle (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2020)
Implementation of human resource management for educators is a very important role. professional human resource educators will produce quality and learning and education. However, one of the problems that often occurs in the implementation of management for educators is if they do not use systems and good management governance. This usually happens due to the lack of serious attention from related parties such as foundations and head of school or other stake holders who have responsibilities and important roles in developing the quality of educational institutions. The problems that occur in MA Al-Hilaal Tehoru are that there is no broad acceptance information, no selection system is applied either for administration or academic test selection, but the placement of teachers is based on academic educational background, but there are other things that are very important to explore related to structural from the Al-Hilaal Tehoru foundation because in general there is no administrative and organizational involvement with the schools they support. The focus of this research is the implementation of acceptance, selection and placement for teaching staff in MA Al-Hilaal Tehoru, Tehoru sub-district, Central Maluku Tengah. This type of research is descriptive research, qualitative approach, data sources are primary data, and secondary data. Data collection techniques are through interview guidelines, Observation sheets and documentation. Based on the findings of the results of this study are; a) Implementation of admission management is done for educators but the admission information is not through the method of publicity so that applicants meet directly with the principal in the office room. b) the selection process is carried out by the school, but the concept of the procedure is not carried out in an integrated manner because prospective educators applying for graduation are considered to have academic qualifications and are considered to have educational background so that they are considered capable. c) the placement has been carried out based on a meeting with the principal, so that all educators are placed according to their knowledge and expertise and the school involves educators from other schools if the position of the subject has no educator to support it.